Предмет: Математика,
автор: darcy28
3x-(4x-11) при x=-6
помогите плиз
Ответы
Автор ответа:
2
Ответ:
17
Пошаговое объяснение:
= 3х - 4х + 11 = -х + 11
Х = -6
(-1 * (-6) ) + 11 = 6 + 11 = 17
Автор ответа:
1
Ответ:
17
Пошаговое объяснение:
3x-4x+11=-x+11.
x=-6
(-1*(-6))+11=6+11=17
Похожие вопросы
Предмет: Другие предметы,
автор: Arina657
Предмет: Русский язык,
автор: kseniya0945
Предмет: Окружающий мир,
автор: АлександраСеливанова
Предмет: Литература,
автор: lyuba3462
Предмет: Немецкий язык,
автор: veronikazrn